(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The research analyses the effects of urbanisation on street children in Lusaka, Zambia, by investigating their living situations, service access, and mental well-being. Using a mixed-methods research design, the study combines quantitative survey results with qualitative interview data to generate complete knowledge about these effects. The researchers recruited 80 street children through purposive sampling with local NGOs who assisted in the selection process. These children ranged from 6 to 17 years of age. The research shows that fast urban expansion leads to a 70% increase in street homelessness and causes education and healthcare barriers, as 65% have irregular schooling and 75% lack stable healthcare. The research demonstrates that older children specifically experience increased psychological distress because 75% of them reported violence or exploitation. According to qualitative findings, these children display remarkable resilience because many want to pursue education and achieve a better future, even though their situation is complicated. The study determines that protective and policy measures must be established because safe residential arrangements, available education and healthcare, more substantial child protection services, and family reunification efforts are essential. Research evidence demonstrates the immediate necessity to reduce the negative impact of urbanisation on street children while promoting their social integration.